Kaleidoscope of Poland : A Cultural Encyclopedia - Swan, Oscar E.; Kołaczek-Fila, Ewa (Book collections on Project MUSE., 2015)
"Kaleidoscope of Poland is a highly readable volume containing short articles on major personalities, places, events, and accomplishments from the thousand-year record of Polish history and culture. Featuring approximately 900 compact text entries and 600 illustrations, it will be a handy reference at home, a perfect supplement to traditional guide books when traveling, an aid to language study, or simply browsed with enjoyment from cover to cover by anyone with an interest in Poland. The entries describe essential features of Poland from the mundane to the sublime. Whether it is bagels or the Bug River, Chopin or Madame Curie, the authors offer colorful and often witty snapshots of significant individuals, customs, folklore, historic events, phrases, places, geography, and much, much more. Beginning with the emergence of the Polish state in 966 under Mieszko I, to the resurrection of present-day Poland within the European Union, it's also a sweeping account of the tumult and triumphs the nation has witnessed through much of its history. This highly entertaining yet informative book is essentially a 'cultural dictionary, ' offering a knowledge base that can be referred to time and time again. Kaleidoscope of Poland will be welcomed by readers of Polish descent, students of Polish, or anyone planning to visit Poland--anyone seeking a greater insight into this fascinating land"--